Analysis of the chemical interaction of polyhexanide with endodontic irrigants - Z. S. Zurab; Yu. A. Generalova; A. A. Kulikova; A. Yu. Umarov; F. V. Badalov; A. Wehbe; E. M. Kakabadze (Эндодонтия Today)
INTRODUCTION. Chronic apical periodontitis (CAP) poses significant challenges in endodontics due to microbial resistance and inadequate disinfection protocols. Polyhexanide (PHMB) is a promising irrigant due to its antimicrobial properties. However, its interactions with other commonly used endodontic irrigants require further investigation to establish effective and safe clinical protocols. AIM. To evaluate the chemical interactions of PHMB with sodium hypochlorite (NaOCl), hydrogen peroxide (H2O2), EDTA, and chlorhexidine and identify optimal irrigation protocols.MATERIALS AND METHODS. The study utilized high-performance liquid chromatography (HPLC) to monitor reactions of PHMB with NaOCl, H2O2, EDTA, and chlorhexidine at intervals of 30 minutes, 1 hour, and 3 days. The analysis focused on detecting reaction products and assessing chemical stability.RESULTS. PHMB formed a precipitate when combined with NaOCl, leading to its complete depletion in the solution. Reaction with H2O2 produced new chemical compounds, while EDTA demonstrated no significant negative reactions. Mixtures with chlorhexidine generated new products and precipitates. Sequential use of EDTA and PHMB showed compatibility and potential for effective irrigation.CONCLUSIONS. Polyhexanide is a valuable irrigant for endodontics, particularly in combination with EDTA, as it provides smear layer removal and antimicrobial action without adverse interactions. Sodium hypochlorite and hydrogen peroxide require careful protocol adjustments to avoid chemical incompatibility. Further studies are necessary to confirm the clinical outcomes and refine protocols for safe and effective endodontic treatments.